Physical punishment and effective verbal communication in children aged 9–36 months, according to sex: secondary analysis of a national survey - Illachura, Vanessa Chire (2024)
Background: A substantial number of children in the world are regularly subjected to physical punishment by their parents as a method of upbringing. Evidence suggests that it has negative effects on the development of brain function. However, evidence regarding its association with verbal communication is limited and heterogeneous. It is also unknown whether the effects are the same in both boys and girls; especially in the contexts of developing countries, where the highest rates of physical punishment are found. Objective: This investigation aimed at analyzing the association between physical punishment administered by both fathers and mothers and effective verbal communication among children aged 9–36 months according to sex. Methods: A secondary analytical cross-sectional study was conducted based on the 2018–2019 Peruvian Demographic and Family Health Survey. Physical punishment, based on the mother’s report of the use of hitting and/or slapping, was considered as a method to correct children by the father and/or mother. Effective verbal communication (EVC) was measured using the Battle scale which consists of age-appropriate questions included in the early childhood development module. A generalized linear model of the family and Log Poisson link option was used to identify the association between them, using the crude, general adjusted, and sex-stratified models. Results: Of all the children, 16.31% received physical punishment from their father and/or mother, wherein 16.65% were boys and 15.97% were girls. Moreover, 36.48% exhibited EVC, wherein 32.55% were boys and 40.50% were girls. Adjusting for socioeconomic level, witnessing violence, mother’s marital status, age, occupation, education level, language, number of children, and moderate-to-severe depressive symptoms, it was found that boys who received physical punishment from their father and/or mother have a 31% lower probability of EVC (adjusted prevalence ratio (aPR) 0.69, 95% confidence interval (CI) 0.58–0.83, p < 0.001), whereas no association was found in girls who received physical punishment from their father and/or mother and EVC (aPR 0.93, 95% CI 0.81–1.06, p = 0.278). Conclusions: An association was found between physical punishment administered by father and/or mother and reduced EVC among boys, whereas no such association was found among girls. It is possible that even though a significant impact has not been observed in girls during this early stage, they may experience consequences in later stages of life, further research is needed.